Immunological abnormalities in lichen planus - Ostrowska, Aleksandra; Susło, Anna (Dermatology Review/Przegląd Dermatologiczny, 2022)
Lichen planus is a chronic disease associated with the occurrence of characteristic papular pruritic lesions. The most significant immunological markers of lichen planus are cytokines. Numerous publications showed changes in the serum level of tumor necrosis factor, interferon g, interleukins 2, 4, 6, 8, 10, 17 and 22. Early lichen planus is associated with a high number of macrophages, T cells, and dendritic cells, while advanced lichen planus with a high number of Treg cells. There is no single specific marker for lichen planus, but certain cytokine levels can be used as a prognostic factor for disease progression and as an indicator of treatment response. Analysis of the immune markers can help to define the disease stage and lichen planus subtype, but histopathology still remains a standard in lichen planus diagnosis.